Development of a Cryopreservation Protocol for In Vitro Buds of South African Sweet Potato Accessions - Manamela, Machoene Tshidi (University of the Witwatersrand, Johannesburg, 2025)
Cryopreservation improves and strengthens the conservation of sweet potato (Ipomoea batatas) accessions conserved in the field gene bank and tissue culture at the South African National Plant Genetic Resources Centre (NPGRC). Cryopreservation is usually achieved at -196°C in liquid nitrogen (LN) in which the metabolic functions of the material are halted. Field gene bank and tissue culture conservation methods are used for short to medium term conservation. Cryopreservation approaches need to be developed to effectively conserve sweet potato for long-term conservation because currently, there are no long-term conservation methods used. The encapsulation-vitrification method using plant vitrification solution 2 (PVS2) is generally used for crop species, but the success varies depending on the cultivar. In this regard, modifications were needed to obtain successful cryopreservation of the sweet potato accessions of the South African NPGRC. It was believed that the encapsulation-vitrification method using PVS2 as a cryoprotectant would result in a higher percentage of regeneration compared with other cryopreservation methods. This study aimed to assess the buds’ viability, water content and optimise the concentration and duration of exposure to cryoprotectants for successful cryopreservation, using the encapsulation-vitrification method. The use of PVS2 resulted in no plant regeneration after retrieval from liquid nitrogen (LN) suggesting that it may have been toxic to these accessions. Therefore, it was important to understand the impact of the individual and combination components of PVS2 on the viability of the buds of sweet potato. The suitable concentration of combination components of PVS2 was PVS5% which resulted in 93% regeneration. However, the materials did not survive the cooling and rewarming processes indicating too higher water content to survive cooling and rewarming. After treatment with preincubation, preculture, osmoprotection and PVS5% increased the water content from 26 to 72%. Swapping PVS5% with osmoprotection solution reduced the water content to 34%, but the regeneration was negatively impacted. Reducing exposure to the osmoprotection solution to 20 minutes resulted in 70–80% regeneration but did not provide sufficient dehydration for successful cryopreservation. Modified Plant vitrification solution 3 (70%PVS3) applied sequentially with PVS5%, osmoprotection solution and physical dehydration, retained the regeneration rate (83–87%) and no crystallisation during cooling in LN. Recrystallisation occurred only during rewarming process in 1.2 M sucrose at 38-40°C. The combination treatment (PVS-PD) applied in this study exhibited potential in sweet potato cryopreservation and warrants further investigation to refine the rewarming technique following cryopreservation.
A thesis submitted in fulfilment of academic requirements for the Degree of Doctor of Philosophy in Plant Science, to the Faculty of Science, School of Animal, Plant and Environmental Sciences, University of the Witwatersrand, Johannesburg, 2025
Keywords: Cryopreservation; Cryoprotectants; Buds; Sweet Potato; PVS5%; PVS3; Vitrification; UCTD; SDG-15: Life on land; SDG-4: Quality education